Learning from other people's fear: amygdala-based social reference learning in social anxiety disorder. Issue 14 (1st August 2016) - Blair, K. S.; Otero, M.; Teng, C.; Geraci, M.; Lewis, E.; Hollon, N.; Blair, R. J. R.; Ernst, Monique; Grillon, C.; Pine, D. S.
Abstract : Background: Social anxiety disorder involves fear of social objects or situations. Social referencing may play an important role in the acquisition of this fear and could be a key determinant in future biomarkers and treatment pathways. However, the neural underpinnings mediating such learning in social anxiety are unknown. Using event-related functional magnetic resonance imaging, we examined social reference learning in social anxiety disorder. Specifically, would patients with the disorder show increased amygdala activity during social reference learning, and further, following social reference learning, show particularly increased response to objects associated with other people's negative reactions? Method: A total of 32 unmedicated patients with social anxiety disorder and 22 age-, intelligence quotient- and gender-matched healthy individuals responded to objects that had become associated with others' fearful, angry, happy or neutral reactions. Results: During the social reference learning phase, a significant group × social context interaction revealed that, relative to the comparison group, the social anxiety group showed a significantly greater response in the amygdala, as well as rostral, dorsomedial and lateral frontal and parietal cortices during the social, relative to non-social, referencing trials. In addition, during the object test phase, relative to the comparison group, the social anxiety group showed increased bilateral amygdala activation to objects associated with others' fearful reactions, and a trend towards decreased amygdala activation to objects associated with others' happy and neutral reactions. Conclusions: These results suggest perturbed observational learning in social anxiety disorder. In addition, they further implicate the amygdala and dorsomedial prefrontal cortex in the disorder, and underscore their importance in future biomarker developments.